(untitled) (Eurasian Research Bulletin, 2026)
The development of learning motivation is of particular importance for the teacher training system, as only teachers motivated to continuously learn and develop themselves can effectively influence the development of relevant motivation in their students. In this regard, one of the key tasks of higher pedagogical education is developing students’ sustainable motivation for learning and self-development, as highlighted in the Decree of the President of the Republic of Uzbekistan“On approval of the concept of development of the higher education system of the Republic of Uzbekistan until 2030”. Developing the professional identity of teaching students during their professional training is a complex task. Therefore, studying the issue of professional identity in the context of academic motivation during student years could contribute to more effective learning and create favorable conditions for students’ harmonious personal development.